PELATIHAN PENINGKATAN TENAGA KEOLAHRAGAAN TERKAIT TALENT SCOUTING UNTUK PELATIH EKSTRAKULIKULER DAN GURU PJOK - Hamdani; Sapto Wibowo; Muchamad Arif Al Ardha; Mochamad Ridwan; Moh. Fathur Rohman (Universitas Negeri Surabaya, 2025)
Sports talent development is a crucial foundation for building a sustainable sports achievement system. In Magetan Regency, talent identification is still commonly conducted naturally without scientific approaches, leading to suboptimal development of young athletes' potential. This community service focuses on enhancing the capacity of physical education (PE) teachers and sports coaches to identify students' sports talents using the sport search method supported by information technology. The program aims to equip participants with skills to apply physical tests, psychological questionnaires, and behavioral observations to help determine the most suitable sports disciplines. The implementation methods include preliminary studies, material and instrument development, pilot training, full-scale training, monitoring, and dissemination. The results show significant improvement in participants’ knowledge and skills, along with refinement of the sport search instruments based on feedback. This program is expected to accelerate talent development and improve sports quality in Magetan Regency systematically and sustainably.